Money demand: A simple look at some data - Juan Pablo Nicolini (Aussenwirtschaft, 2017)
In this paper, I offer a non-technical summary of recent research that focuses on the stability properties of real money demand. I first describe a simple workhorse model that serves as a conceptual framework for organizing the data and guiding the empirical analysis. Then, by using simple plots, I argue that the implications of the simple theory are remarkably robust over time. I do this for some developed economies with a history of relatively low inflation and for two developing economies that experienced severe hyper- inflation. Finally, we point toward several failures in this research and discuss avenues for future work.
Keywords: 330